How patients in Denmark acquire their medicines: overview, data sources and implications for pharmacoepidemiology. Issue 1 (28th July 2020) - Jensen, Thomas B.; Andersen, Jon T.; Jimenez‐Solem, Espen; Lund, Marie
Abstract: The means by which patients acquire their medications differ between countries, and a knowledge of this is essential when conducting and interpreting pharmacoepidemiological studies. The aim of this paper is to provide an overview of how patients obtain medicines in Denmark, to relate these to nationwide registries available for research and to discuss the implications for research. Health services are predominantly tax‐funded in Denmark, with dentistry and some medicine bought at community pharmacies being exceptions, involving partial reimbursement of charges. The paper gives an overview of prescription medicines acquired from community pharmacies (including magistral preparations), over‐the‐counter medicines, vaccinations and in‐hospital medicine including so‐called "free medicine" (in Danish: "vederlagsfri medicin"). "Free medicine" is medicines for a defined list of diseases and indications that is provided free of charge to patients in outpatient clinics. The paper also describes the content of the various Danish data sources about medicine use, summarizes their strengths and limitations, and exemplifies the ways of evaluating their completeness. An example is provided of the regional variation in the means by which medicines are acquired.